Post-Filter Design for Superdirective Beamformers with Closely Spaced Microphones - Löllmann, Heinrich; Vary, Peter (IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA), 2007)
In this paper, the post-filter design for superdirective beamformers with small microphone arrays is investigated, which can be used for speech enhancement systems in mobile communication devices or digital hearing aids. It is shown that coherent noise sources can be well suppressed by a multi-channel controlled post-filter. However, a sufficient suppression of diffuse noise sources can not be achieved by this. Such noise can be further reduced by a single-channel controlled post-filter. This combined post-filter design leads to a significantly better speech quality compared to the related approach of Le Bouquin et al.